Assessment of Self-Esteem Among Tunisian Cannabis Users. (1st June 2022) - Brahim, S.; Henia, M.; Haj Mohamed, A.; Aoun, M.H.; Zarrouk, L.
Abstract : Introduction: Cannabis is among the most widely used substances in the world. it is associated with several mental health problems. Objectives: To assess self-esteem among a group of young Tunisian users of cannabis. Methods: The total study sample was composed of 137 participants, who took part of a transversal descriptive study during two months (January and February 2020). Results: In our study population, the cannabis consumers were young adults aged between 18 and 35 years old, with a male predominance of 71%. Among those users, 65.9% were single and 29.7% dropped out of school or experienced academic failure. On a socio-economic level, we concluded to a rate of 5.8% (lower class), 60.9% (middle class) and 33.3% (upper class). Besides, 40.8% were employed. In total, 23.2% had a psychiatric history. Furthermore, the use of other substances was also prominent and frequent as follows: alcohol 72.5%, tobacco 74.6%, ecstasy 41.3% and 25.4% cocaine. The use of cannabis was considered as a means of indulgence and pleasure for 66.7%, as an anxiolytic for 26.8% and as a sedative for 23.9%. Self-esteem, among those cannabis users, was very low in 20% of cases, low in 38% of cases, medium in 15% of cases and high in 25% of cases. Conclusions: These results lead us to question the relation between cannabis and self-esteem. The question that is evolved about the use of cannabis is the following: Is it used as a remedy or is it the cause of self-esteem deficiency? Disclosure: No significant relationships.